Study of Antibiotic Smart Use Project at Maeon Hospital, Maeon district, Chiangmai - กริชนิกรกุล, ปาริชาต (Journal of Nakornping Hospital, 2019)
Antibiotics Smart Use (ASU) has been implemented at Maeon hospital since 2011. The purpose of ASU is to reduce unnecessary antibiotic prescription and cost among 3 common diseases, upper respiratory tract infection (URI), acute diarrhea and simple wound infection. A descriptive study was performed to evaluate the project. Antibiotics prescription rate and cost among patients came with 3 common diseases during October 1st, 2011- September 30th, 2014 were compared with the rate of antibiotic use and cost during October 1st, 2010- September 30th, 2011. Result of treatment and rate of appreciation among cases were also evaluated. Results: Rate of cases who didn’t get antibiotic among 3 common diseases were increasing to 10.74 %, 24.78 %, and 64.44 % in 2012, 2013 and 2014, respectively. When compare to the rate of antibiotic free in 2011, the changing rate of antibiotic free among simple wound infection was the highest, i.e. 15.63 %, 71.45 %, 105.33 % in the year 2012, 2013, and 2014, respectively. While changing rate of antibiotic free among URI were 6.84 %, 23.42 % and 61.86 %. The changing rates of antibiotic free among acute diarrhea were 16.75 %, 15.23 and 58.56 %. When compare to the financial cost of antibiotic before starting the project, the cost were 15 %, 26, and 30 % reduced in the year 2012, 2013 and 2014. From interviewing the patients about the result of treatment, 97 % of them felt good or better while only 3 % of them felt worse. For satisfaction of treatment, more than 85 % of them satisfied. From this study has shown that rational antibiotic use project can reduce rate of antibiotic used and financial cost with high better treatment result and satisfaction. Continuing and expanding rational antibiotic use to all health sectors will be very useful for the country.